Surviving Your Dissertation: A Comprehensive Guide to Content and Process. - Salamon, Gerald L.; Moriarity, Shane R. (The Accounting Review, 1993)
Reviews the book "Surviving Your Dissertation: A Comprehensive Guide to Content and Process," by Kjell Erik Rudestan and Rae R. Newton.